EXPLANTATION BY OSTEONECROSIS AFTER WISDOM TOOTH EXTRACTION - de Oliveira, José Eudes Protázio; de Souza, Vilton Zimmermann; de Souza, Gabriel Baldissera; de Andrade, Taysnara Ismaeley; Vieceli, Eduardo Panceri; Figueiredo, Fábio Castanha; Garcia, Gislaine Felipe; Manfro, Rafael (Seven Editora, 2024)
Osteonecrosis, defined as the death of bone tissue due to lack of blood supply, is a pathological condition that, associated with predisposing factors, can affect the gnathic bones, exacerbating the inflammatory process due to the wide oral microbiota, and can significantly affect the quality of life of patients. Patients with skeletal disorders that induce bone loss, such as osteoporosis, make continuous use of antiresorptive drugs in order to alter bone remodeling. The objective of this study is to describe a case report of the treatment of osteonecrosis of the jaws induced by denosumab, discussing clinical-pathological aspects of the disease. This article highlights the case of patient R.S.B.K., 78 years old, who was affected by breast cancer, for whom she underwent chemotherapy treatment for 5 years. He suffered a pathological rib fracture, where he started treatment with an anti-resorptive drug called Denosunab. After dental extraction of element 28, a local infectious inflammatory process involving adjacent implants began, which culminated in unsuccessful surgical interventions. After the end of the half-life of the medication, the return of tissue functions was observed, evolving with bone coverage by the oral mucosa. It is concluded that the correct and early diagnosis is essential, combined with a resolutive treatment through a conservative approach, improving the quality of life of patients. DOI:https://doi.org/10.56238/sevened2024.031-048